Estimasi Populasi dan Habitat Rusa Timor (Rusa timorensis Blainville1882) dalam Kawasan Taman Wisata Alam Menipo - Elisa Iswandono; Hariany Siappa; Oktavianus Alvanaidi Sene; Marliana Chrismiawati; Yeni Trisetyaningrum; Beatrix Luisa Wisang (Institut Pertanian Bogor, 2024)
Knowing the population and habitat conditions of Timor Deer (Rusa timorensis), which is a protected animal, is very important to ensure the survival of this species. One of the most important habitats for Timor Deer is Menipo Nature Park, which must be well managed to support the welfare and sustainability of the species. Good management includes protection of natural habitats, regular population monitoring, and sustainable conservation efforts so that Timor Deer can survive in their natural environment. The purpose of this study was to estimate the population and habitat conditions of Timor deer in Menipo. The method used is a combination of point and path, while the habitat is described descriptively. From the results of research on the 571 ha habitat area, the population of timor deer was estimated to be 399 individuals with a population range of 366 to 432 individuals at the 95% confidence interval with a population density of 1.14 individuals per hectare. The population structure showed an inverted pyramid, indicating less than optimal conditions in terms of population age distribution. The sex ratio was 2:5 for juveniles, 2:3 for adults, and 1:1 for the old age group. This sex ratio is not good for the timor deer population as 1:5 is good. The most common type of grass for deer is timor grass (Ischaemum timorensis). Other grass species are Microlaena stipoides, Paspalum scrobiculatum, Imperata cylindrical, and Desmodium capitulum shrub. However, some areas of this habitat are covered by alien invasive species, Cromolaena odorata, which needs to be eradicated to maintain food availability. Mangrove parts eaten by Timor deer (Rusa timorensis) include young leaves, young stems, and exfoliated bark. Mangrove species commonly found as food for deer include Rhizophora mucronata, Bruguiera parviflora, and Sonneratia alba. Keywords: habitat, Menipo, population, timor deer, Rusa timorensis